Alteration of Ecological Network of Ukraine: Problems are from the Point of Geographer - Denisik, G. I. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
The problems of alteration of ecological network ofUkraineand its separate regions are considered; it is marked that forming of ecological network is possible only on the basis of cultural landscape, and at first it needs modern anthropogenic landscapes’ optimization. An author perceives critically to Europenian strategy of a landscape and plants and animals variety maintainance and he cautions against its unthinking over application inUkraine.